Epidemiology of Salivary Gland Lesions in Referring Patients to Isfahan University of Medical Sciences Hospitals 1998-2003 - B Movahedian; R Noori; M Rezaei (Isfahan University of Medical Sciences, 2007)
Introduction: Salivary gland lesions, as a diverse group, can be classified as infectious, inflammatory and neoplastic. These lesions have been considered rare and few multitude epidemiologic studies in Iranian populations are noticeable.Methods and Materials: 574 (314 men and 260 women) cases diagnosed as salivary gland lesions were studied. The sample comprised of 198 benign lesions, 113 malignant and 263 nonneoplastic ones. The lesions were further classified with regard of age, sex, site and histopathology.Results: Patients' files, 314 men and 260 women, were assessed. The diagnosis included 46% to be non-neoplastic, 34% to be benign and 20% to be malignant. The most common benign lesion was pleomorphic adenoma (68.1% of benign tumors and 23.5% of all lesions). Benign tumors were more frequent, in the age group of 31-50 years. Mucco-epidermoid carcinoma was the most common malignant tumor (40% of malignant tumors, and 7.8% of all lesions); most of the malignant lesions were seen to occur by the age of more than 50. Forty-six percent of all lesions were non-neoplastic which comprised of both genders (56.3% men, 43.7% women). Chronic sialadenitis was the most frequent lesion years.Conclusion: Present study showed that pattern of salivary gland lesions epidemiology is different to series studies from all over the world, even though it was similar to the others partly. Such a difference points out the role of geographic and racial factors. Key words: Salivary glands, Epidemiology, Neoplastic lesions, Non-neoplatic lesions,inflammatory lesions